Manufacturing Technique of Aluminum Plate Waste Crusher - Imadudin Abdurohim; Prasetyo; Albert Daniel Saragih (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2021)
With the increase in the amount of unused aluminum plate waste every year, it can increase environmental damage if no preventive measures are taken, so it must be done processing the unused plate waste by recycling. One of the recycling processes is by destroying it before it is thawed. The plate crusher is designed to have dimensions (861 mm x 250 mm x 910 mm), with the main power being an electric motor of 0.5 HP (0.37 kW) and a motor shaft rotation of 1400 rpm. The type of knife used has dimensions of 100 mm x 10 mm which have a disc-like shape that has 4 cutting blades at each end. The tool is designed to use two rotating shafts with 10 crushing blades placed on each part of the shaft. The crusher is designed using the Solidworks Application.